Assertiveness Training dalam Penurunan Risiko Perilaku Kekerasan pada Pasien Skizoprenia - Dwiyantoro, Dwiyantoro; Hamid, Achir Yani Syuhaimie; susanti, Herni; Fauziah, Fauziah (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the implementation of Assertiveness Training (AT) in reducing the risk of violent behavior in schizophrenia patients. The method used by researchers is a single instrumental study with a collection process based on scanning data and integrated patient progress records to evaluate each existing activity and development. The study's results showed that after being given Assertiveness Training (AT), the signs and symptoms of violent behavior decreased, and the ability to overcome the risk of violent behavior increased. So, it can be concluded that providing Assertiveness Training (AT) to patients who are at risk of violent behavior can reduce behavioral signs and symptoms at risk of violent behavior and increase ability. The conclusion is that providing Assertiveness Training (AT) to patients who are at risk of violent behavior can reduce behavioral signs and symptoms of risk of violent behavior and increase ability. Keywords: Assertiveness Training, Schizophrenia, Risk of Violent Behavior